New drug Delivery System A Novel Way for Unani Dosage Form (A Review) - Fahamiya, N.; Aslam, M. (Faculty of Unani Medicine, Aligarh Muslim University, 2010)
Various dosage forms are in practice in Unani system since long...
Keywords: Drug delivery; Nanoparticles; Unani Medicine